1999
DOI: 10.1016/s0895-7061(98)00274-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of electronic pill boxes to assess risk of poor treatment compliance Results of a large-scale trial

Abstract: The objective of the present study was to determine the predictive factors of treatment compliance in hypertensive patients. This was an open large-scale multicenter study where mild to moderate essential hypertensive patients received trandolapril (2 mg) once daily for 30 to 60 days in addition to their usual treatment. Trandolapril was packed in electronic pill boxes that registered date and time of each opening. The main compliance parameters were the percentage of missed doses, the percentage of delayed do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
8

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 24 publications
3
22
0
8
Order By: Relevance
“…This is fully in line with the current ESH/European Society of Cardiology guidelines suggesting use of all drug regimens in patients with cerebrovascular disease provided that BP is effectively reduced [18]. In a smaller study using electronic pill boxes to assess treatment compliance, female gender was associated with a better outcome in terms of compliance [23].…”
Section: Hypertension Controlsupporting
confidence: 79%
“…This is fully in line with the current ESH/European Society of Cardiology guidelines suggesting use of all drug regimens in patients with cerebrovascular disease provided that BP is effectively reduced [18]. In a smaller study using electronic pill boxes to assess treatment compliance, female gender was associated with a better outcome in terms of compliance [23].…”
Section: Hypertension Controlsupporting
confidence: 79%
“…ACEI, angiotensinconverting enzyme inhibitor; ARB, angiotensin receptor antagonist; CA, calcium antagonist. treatment is influenced also by the density of the population in the geographical area where patients live, with a maximal disadvantage for residents of metropolitan areas, as also shown by Vaur et al[36] for the Paris area. This means that adherence to the prescribed antihypertensive treatment regimen does not only depend on doctor's behaviour (type of prescription) and individual patient characteristics, but it extends to social and environmental factors.…”
mentioning
confidence: 59%
“…Vaur et al [7] monitored compliance by using MEMS caps in a study of 2173 hypertensive patients and found that 37% had poor compliance (< 80% correct dosing periods).…”
Section: Compliancementioning
confidence: 99%